PENGARUH KEADILAN ORGANISASIONAL DAN JOB INSECURITY TERHADAP QUIT INTENTION DI PT BALI CHIPPENDALE FURNITURE - Anggara Putra, I Putu Agus Dian; Rahyuda, Agoes Ganesha (E-Jurnal Manajemen, 2017)
This study aims to determine the effect of organizational justice and job insecurity intention to quit the employees of PT Bali Chippendale Furniture. The population in this study were employees of PT Bali Chippendale Furniture totaling 116 people. The samples in this study conducted with pr oportionate rondom sampling approach because the sample frame is already known such as number of employees, while the sampling method used in this study refers to the approach Slovin. Based on these criteria the number of employees who qualify as a sample of 54 employees. The analytical tool used is multiple linear regression analysis. The results obtained in this study is the distributive justice negative effect on quit intention, procedural fairness negative effect on quit intention, interactional fairness negative effect on quit intention and job insecurity positive effect on quit intention.
Keywords: job insecurity, distributive justice, interactional justice, procedural justice, quit intention